Tarbiyah Berbasis Khudi: Menempa Karakter Mandiri dan Kreatif Ala Muhammad Iqbal - Rofi Anisa, Dian; Auliya Safitri, Dinda; Puspika Sari, Herlini (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Modern education often falls short in nurturing character, as it tends to prioritize cognitive achievement over holistic development producing students who excel academically but lack independence, creativity, and moral strength. This study seeks to explore the concept of Tarbiyah Based on Khudi (Ego/Selfhood) inspired by Muhammad Iqbal, positioning it as a philosophical and pedagogical framework to address the current character crisis and cultivate Independent and Creative individuals toward the realization of Insan Kamil (the Perfect Human). Employing a qualitative method through a library research approach, this study conceptually examines the three fundamental pillars of Khudi development: Obedience (Ita’at)/Discipline, Self-Mastery (Dabt-i-Zabt)/Self-Control, and Vicegerency (Niyabat-i-Ilahiyyah)/Creativity. The findings indicate that Khudi-based Tarbiyah serves as an effective integrative framework. Genuine independence arises from self-control, fostering responsible freedom and autonomy, while creativity embodies the essence of vicegerency through a continuous spirit of Ijtihad that drives social innovation and civilizational progress. Ultimately, Khudi ensures spiritual independence and moral vitality. The study recommends adopting progressive and dynamic learning models such as project-based learning aligned with the Khudi philosophy to integrate affective and psychomotor dimensions into Indonesia’s character education.